Methods for Ex Ante Economic Evaluation of Free Trade Agreements - David Cheong (Asian Development Bank (ADB), 2010)
This paper provides practical techniques to policymakers for evaluating the potential economic effects of a Free Trade Agreement (FTA). To this end, the paper discusses how to apply three methods: (i) trade indicators, (ii) SMART (Software for Market Analysis and Restrictions on Trade) in WITS (World Integrated Trade Solutions), and (iii) the GTAP (Global Trade Analysis Project) model. The paper identifies the different aspects of an FTA that each method can evaluate, describes data sources and software requirements, specifies how to interpret the output from each method, and discusses the strengths and limitations of each method. To illustrate each method, there are examples applied to countries in the Association of Southeast Asian Nations (ASEAN), particularly Cambodia, Lao People`s Democratic Republic, and Viet Nam.
hdl:11540/1951
Keywords: F13; F15; 330; regionalization; evaluation methods; trade indicators; SMART model; CGE analysis; preferential trade agreements; Asia